Propuesta para el aprendizaje de división de redes en subredes utilizando gamificación - Herrera Romero, Brithany Maribel (2024)
This study addresses the need for innovative pedagogical methods in the teaching of networks, by integrating gamification for the division of networks into subnetworks and the use of subnetwork masks. Gamification strategies were implemented within the theoretical curriculum, demonstrating a marked improvement in student understanding and retention, as evidenced by evaluation results. Student participation and enthusiasm increased, highlighting the effectiveness of the interactive approach. This pedagogical contribution marks a significant advance, aligning with current educational trends and promoting more dynamic and effective learning.